An 8–18 GHz power amplifier with novel gain fluctuation compensation technique in 65 nm CMOS *Project supported partly by the National Natural Science Foundation of China (No. 60123456) and partly by the National 13th Five-Year Project. (December 2018) - Gong, Jie; Li, Wei; Hu, Jintao; Ye, Jiao; Wang, Tao
Abstract: A wideband CMOS power amplifier with high gain and excellent gain flatness for X–Ku-band radar phased array is proposed in this paper. Excellent gain flatness is achieved with transformer based matching networks (TMNs), in which the gain fluctuation of an inter-stage matching network can be compensated by the proposed design methods. The circuit is fabricated in the TSMC 65 nm RF CMOS process. The proposed technique is verified by the measurement results, which show that the wideband PA achieves gain of 21–22.5 dB with only ±0.75 dB gain fluctuation and 13–14.6 dBm flat output power between 7.5 and 15.5 GHz, and a little more ripple in the rest of the X–Ku band due to the inaccuracy of passive modelling at high frequency. The circuit delivers saturated and 1 dB-compressed output power of 14.6 and 11.3 dBm respectively at 13 GHz, for a maximal power-added efficiency (PAE) of 23%.